Pola Pengasuhan Orang Tua Muslim Suku Jawa dan Dayak pada Anak Usia Dini di RA Al-Azhar Palangka Raya - Bismillah, Alfi; Muzakki, Muzakki; Aghnaita, Aghnaita (Faculty of Education and Teacher Training of UINSI Samarinda, 2026)
This study aims to compare the parenting patterns of Muslim parents from the Javanese and Dayak tribes in early childhood in RA Al-Azhar Palangka Raya. The research uses a descriptive qualitative approach, with data collection techniques including observation, interviews, and documentation. The research informants consisted of 20 parents whose children were in group B and who had Javanese and Dayak cultural backgrounds. Data analysis is carried out through data condensation, data presentation, and drawing conclusions using triangulation to ensure data validity. The results of the study show that Javanese parents tend to emphasize affection and the cultivation of social norms in childcare. In contrast, Dayak parents place greater emphasis on children’s involvement in traditional activities. These findings show that cultural background plays an essential role in shaping parenting patterns and the process of shaping early childhood social character and identity. The novelty of this research lies in its cross-cultural comparative analysis of early childhood education, which makes an empirical contribution to the development of culturally sensitive parenting and educational practices in Indonesia.